The transformation of propaganda: The continuities and discontinuities of information operations, from Soviet to Russian active measures - Horbyk Roman; Prymachenko Yana; Orlova Dariya (Nordic Journal of Media Studies, 2023)
This article focuses on the transformation of Soviet Cold War propaganda into the contemporary Russian information operations, bringing together two distinct periods characterised with the rise of new and sophisticated techniques. By comparing propaganda instructions in KGB manuals and the practices of the propagandists behind the 2014–2020 Secondary Infektion campaign, we find out what of the “analogue” Cold War propaganda remains in the present-day computational propaganda and how exactly Soviet propaganda techniques evolved into the new mediascape. This highlights both strong continuities of methods and techniques and certain discontinuities. Our analysis also contributes to the understanding of the very concept of propaganda, singling out such aspects as covertness, negativity, and inauthenticity as especially ingrained features of the Russian style of propaganda that are also regrettably often overlooked in generic definitions.